2016
DOI: 10.1002/admi.201600418
|View full text |Cite
|
Sign up to set email alerts
|

A New Look at the Electronic Structure of Transparent Conductive Oxides—A Case Study of the Interface between Zinc Magnesium Oxide and Cadmium Telluride

Abstract: and photovoltaic cells. [1][2][3][4] In CdTe-based thin film solar cells, TCOs are employed as front contact layers, which, due to the superstrate configuration of such cells, form the base layer onto which CdTe absorbers are deposited. Thin-film devices based on CdTe have achieved a notable market share as a cost-effective alternative to silicon, with a current world record cell efficiency of 22.1%. [5,6] At a module level, efficiencies have reached 18.2%, which surpasses the best-recorded multi-crystalline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…For a different buffer layer (Zn,Mg)O, it was suggested that such tails are relevant for the charge carrier transport, while the spectral main edges are relevant for the optical properties. [51] Using the main edges, we derive a surface band gap of 3.14 (AE0.14) eV, which is within the region of reported bulk Zn(O,S) band gap values of 2.6-3.4 eV, depending on the S/(S þ O) ratio. [6,52,53] The direct comparison of the band extrema allows a first approximation of the band alignment at the interface, suggesting no pronounced discontinuity in the conduction band and a significant negative valence band offset of %À1.5 eV.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For a different buffer layer (Zn,Mg)O, it was suggested that such tails are relevant for the charge carrier transport, while the spectral main edges are relevant for the optical properties. [51] Using the main edges, we derive a surface band gap of 3.14 (AE0.14) eV, which is within the region of reported bulk Zn(O,S) band gap values of 2.6-3.4 eV, depending on the S/(S þ O) ratio. [6,52,53] The direct comparison of the band extrema allows a first approximation of the band alignment at the interface, suggesting no pronounced discontinuity in the conduction band and a significant negative valence band offset of %À1.5 eV.…”
Section: Resultssupporting
confidence: 74%
“…For a different buffer layer (Zn,Mg)O, it was suggested that such tails are relevant for the charge carrier transport, while the spectral main edges are relevant for the optical properties. [ 51 ] Using the main edges, we derive a surface band gap of 3.14 (±0.14) eV, which is within the region of reported bulk Zn(O,S) band gap values of 2.6–3.4 eV, depending on the S/(S + O) ratio. [ 6,52,53 ]…”
Section: Resultssupporting
confidence: 72%
“…However, these linear extrapolations leave substantial spectral tails undescribed (as shown with the blue linear extrapolation in Figure 6c and blue markings in Figure 6d, leading to a "band gap" of 0.50 (±0.11) eV). While such tails are not uncommon in the description of transparent conductive oxides, 67,68 they are rather unusual in the case of chalcopyrites. We hypothesize that the seemingly narrow "band gap" can be attributed to a much greater number of surface defects compared to its "Cu-poor" counterpart, as we could not find any evidence suggesting the presence of additional binary phases, unique chemical bonding environments, or even any gradual changes in surface composition.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Apart from the quality of a perovskite thin film, which is directly fabricated onto the TCOs in the HTL-free devices, the impact of the TCO substrate on the interface of the TCO/perovskite is also critical for high-performance PSCs. Here, we investigate three different sets of samples using X-ray photoelectron spectroscopy (XPS) to analyze the chemical and electronic structures of the TCO/perovskite interface: (1) TCO, (2) TCO coated with a thin NBG perovskite (≈3 nm), and (3) TCO coated with a thick NBG perovskite (600 nm, i.e., the nominal thickness) films, with ITO, FTO, or IO:H TCOs. In the XPS survey spectra of these samples (Figure S6), all expected TCO signals are detected and attenuated with increasing perovskite thickness.…”
Section: Results and Discussionmentioning
confidence: 99%